1998
DOI: 10.1007/bf02783343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary manganese on arterial glycosaminoglycan metabolism in sprague—dawley rats

Abstract: The objectives of this study were to determine whether dietary manganese deficiency alters total glycosaminoglycan (GAG) concentration and composition and glycosyltransferase activity in rat aortas. Sprague-Dawley rats were fed either a manganese-deficient or a manganese-sufficient diet. Arterial GAGs were isolated and quantified by measuring uronic acid content. The individual GAGs were separated and quantified with cellulose acetate electrophoresis. The activity of the enzyme galactosyltransferase I was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The retardation of growth observed in MnD animals was independent of food intake. Retardation of rodent growth in Mn deficiency has also been reported by previous studies (Paynter 1980;Fahim et al 1990;Klimis-Tavantzis et al 1993;Taylor et al 1997) and it seems to be an effect of reduced efficiency of food conversion with dietary Mn depletion (Yang & Klimis-Tavantzis 1998a).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The retardation of growth observed in MnD animals was independent of food intake. Retardation of rodent growth in Mn deficiency has also been reported by previous studies (Paynter 1980;Fahim et al 1990;Klimis-Tavantzis et al 1993;Taylor et al 1997) and it seems to be an effect of reduced efficiency of food conversion with dietary Mn depletion (Yang & Klimis-Tavantzis 1998a).…”
Section: Discussionmentioning
confidence: 61%
“…In the past we reported a decrease in GalAGs concentration of MnD aortas, but the comparison was conducted between MnD and MnS aortas at the time, since 45-50 ppm was used as a control diet group (Yang & Klimis-Tavantzis 1998a, b). Manganese seems to be specifically required for optimal in vivo activity of the enzyme galactosyltransferase I, which participates in the biosynthesis of rat aortic GAGs (Yang & Klimis-Tavantzis 1998a). The increased concentration of GalAG chains in MnS animals might be attributed to an up-regulation of this Mn-dependent enzyme at concentrations of 45-50 ppm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Mn may affect blood pressure by decreasing the tension of isolated vascular tissue preparations in vitro [21]. However, there have been no animal studies to 0955 Our laboratory was the first to report that Mn plays an important role in maintaining integrity of blood vessels [22][23][24][25][26]. Manganese is involved in arterial glycosaminoglycan metabolism by affecting the total proteoglycan content of the aorta, altering the molecular weight and sulfation pattern of chondroitin sulfate in the same tissue and thus predisposing the vessel to lipid deposition, lipoprotein oxidation and CVD [24,25].…”
Section: Introductionmentioning
confidence: 97%
“…However, there have been no animal studies to 0955 Our laboratory was the first to report that Mn plays an important role in maintaining integrity of blood vessels [22][23][24][25][26]. Manganese is involved in arterial glycosaminoglycan metabolism by affecting the total proteoglycan content of the aorta, altering the molecular weight and sulfation pattern of chondroitin sulfate in the same tissue and thus predisposing the vessel to lipid deposition, lipoprotein oxidation and CVD [24,25]. Manganese is essential for preventing surface damage of the aorta and maintaining the density of the extracellular matrix around smooth muscle cells, especially in the medial layer [26].…”
Section: Introductionmentioning
confidence: 97%